Human bone marrow stromal cells protect prostate cancer cells from TRAIL-induced apoptosis. - Nyambo, R; Cross, N; Lippitt, J; Holen, I; Bryden, G; Hamdy, F; Eaton, C (2004)
UNLABELLED: Tumor-derived OPG has recently been shown to protect prostate cancer cells from apoptosis. This study has confirmed that bone marrow stromal cell-derived OPG also suppresses cytokine-induced apoptosis in this tumor type, suggesting that it may be the presence of bone-derived OPG that is responsible for the observed preference of these cells in colonizing the skeleton. INTRODUCTION: Metastasis to the skeleton occurs in around 70% of patients with advanced prostate cancer (CaP), suggesting that the bone microenvironment may provide factors that favor the growth and survival of prostate cancer cells. Osteoprotegerin (OPG) is a molecule involved in bone remodeling, where it acts as an inhibitor of osteoclastogenesis, but it is also a decoy receptor for TRAIL/Apo 2L, a member of the TNF family of pro-apoptotic cytokines. The aim of this study was to determine whether OPG produced by human bone marrow stromal cells could protect prostate cancer cells from TRAIL-induced apoptosis. MATERIALS AND METHODS: Human bone marrow stromal cell cultures were generated from bone biopsies taken from newly diagnosed untreated CaP patients with (M1) or without (M0) bony metastasis. The stromal origin of these cells was confirmed by Western blot analysis using antibodies raised to stromal and epithelial markers. Media were conditioned over the cultures of these cells for 4 days, and levels of OPG were determined using an ELISA. The human prostate cancer cell line PC3 was challenged with TRAIL (50 ng/ml) in fresh media or in media supplemented with 50% conditioned media, and apoptosis was assessed using DAPI stain. The effects of specific removal of OPG activity by immunoprecipitation or by co-treatment of cultures with an alternative ligand for OPG (RANKL) were also tested. RESULTS AND CONCLUSIONS: The presence of stromal cell conditioned media in PC3 culture significantly reduced TRAIL-induced apoptosis. All stromal cell lines isolated were shown to express OPG and to release this protein into the conditioned media. Immunoprecipitation of OPG and co-treatment of cultures with sRANKL reversed the protective effects of the conditioned media. These data suggest that at least part of the survival advantage gained by CaP cells in colonizing bone may be caused by the production of OPG by tumor-associated stromal cells.